New Sulfanilamide Derivatives Incorporating Heterocyclic Carboxamide Moieties as Carbonic Anhydrase Inhibitors - Andrea Angeli; Victor Kartsev; Anthi Petrou; Mariana Pinteala; Roman M. Vydzhak; Svitlana Y. Panchishin; Volodymyr Brovarets; Viviana De Luca; Clemente Capasso; Athina Geronikaki; Claudiu T. Supuran (MDPI AG, 2021)
Carbonic Anhydrases (CAs) are ubiquitous metalloenzymes involved in several disease conditions. There are 15 human CA (hCA) isoforms and their high homology represents a challenge for the discovery of potential drugs devoid of off-target side effects. For this reason, many synthetic and pharmacologic research efforts are underway to achieve the full pharmacological potential of CA modulators of activity. We report here a novel series of sulfanilamide derivatives containing heterocyclic carboxamide moieties which were evaluated as CA inhibitors against the physiological relevant isoforms hCA I, II, IX, and XII. Some of them showed selectivity toward isoform hCA II and hCA XII. Molecular docking was performed for some of these compounds on isoforms hCA II and XII to understand the possible interaction with the active site amino acid residues, which rationalized the reported inhibitory activity.